The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms8020311
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Gradients Altered the Bacterial Community Composition and Stochastic Process of Rural Polluted Ponds

Abstract: Understanding the effects of pollution on ecological communities and the underlying mechanisms that drive them will helpful for selecting a method to mediate polluted ecosystems. Quantifying the relative importance of deterministic and stochastic processes is a very important issue in ecology. However, little is known about their effects on the succession of microbial communities in different pollution levels rural ponds. Also, the processes that govern bacterial communities in polluted ponds are poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…We prioritized this simple definition over the other complex definition because both definitions essentially reveal the same keystone OTUs. Further, the correlation between the modules and soil environmental factors was investigated through the Mantel test ( Tai et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We prioritized this simple definition over the other complex definition because both definitions essentially reveal the same keystone OTUs. Further, the correlation between the modules and soil environmental factors was investigated through the Mantel test ( Tai et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on tNST, deterministic processes play more important role as compared with stochastic processes. The controversial results of pNST and tNST were also demonstrated in a previous study based on bacterial 16S rRNA amplicon (Tai et al, 2020). This may be due to the calculation of the microbial attributes from different dimensions of diversity (including taxonomic, phylogenetic, functional, etc.).…”
Section: Pathobiome Community Assembly Is Highly Determined By Stocha...mentioning
confidence: 86%
“…Contrary to expectations, there was an increase in Bacteroidetes in the Aquidauana small lake. Although this phylum is more known for adapting well or even preferring polluted environments ​( Da Silva et al, 2015 ; Tai et al, 2020 )​, pollution-sensitive Bacteroidetes have been observed, to function as bioindicators ​( Wolińska et al, 2017 )​. This suggests that our environment might have conditions that are not unfavorable for this group.…”
Section: Discussionmentioning
confidence: 99%